Genetic Diversity of Agronomic Traits in Rice (Oryza sativa L.) Using Several Colchicine Concentrations - Hasan, Erfina N; Husain, Indriati; Yamin, Mayasari; Rahim, Yunnita; Dama, Hasna (International journal of technology and education research, 2025)
This study aimed to evaluate the effects of various colchicine concentrations on the genetic diversity of agronomic traits in rice (Oryza sativa L.). The experiment was conducted at the Agricultural Modernization Application Center (BRMP) Gorontalo from January to April 2025, employing a two-factor factorial completely randomized design (CRD). The first factor was rice variety, comprising two levels: V1 (Inpago 13 Fortis) and V2 (Inpari Nutri Zinc), while the second factor was colchicine concentration with four levels: P0(control/0 ppm), P1 (750 ppm), P2(1000 ppm), and P3 (1250 ppm). Each treatment combination was replicated three times, resulting in 24 experimental units. Observed parameters included both vegetative and generative phases. Results indicated that colchicine did not exert a significant overall effect on either vegetative or generative traits; however, certain concentrations induced an increase in the number of spikelets in the Inpago 13 Fortis variety. In contrast, Inpari Nutri Zinc exhibited higher tolerance to colchicine, maintaining stable growth and morphology across all concentrations. These findings highlight that colchicine effectiveness is highly dependent on dosage and genotype response, emphasizing the need for optimal concentrations to induce mutations without causing toxic effects, thereby providing a foundation for rice mutation breeding.